LENGTH-WEIGHT RELATIONSHIP OF THE SPINNER SHARK (Carcharhinus brevipinna) ON THE CONTINENTAL SHELF OF SOUTHERN BRAZIL - dos Santos, Paulo Roberto Santos; Santoro, Prianka; Chelotti, Luiza de David (Arquivos de Ciências do Mar, 2018)
Here we present the weight-length relationship of the spinner shark (Carcharhinus brevipinna) on the continental shelf of southern Brazil, estimated from an analysis of 125 specimens. No significant differences between males and females, so the data were grouped in equation W = 0,003L3.1534. The results presented here are the first to approach sharks above 75 cm and confirm the positive allometric growth of the species.